Leukemia Virus Activation in Chronic Allogeneic Disease - Hirsch, M. S. (1970)
Young adult (BALB/c × A/J)F(1) hybrid mice have no detectable leukemia viruses. When inoculated with parental BALB/c spleen lymphoid cells, also free of detectable virus, leukemia viruses rapidly become activated in the injected host. Because of similarities between such graft-induced allogeneic disease and spontaneous autoimmunity, it is proposed that autoimmune reactions may activate latent viruses.